Filtration of random solutions of a system of linear difference equations with coefficients depending on a Markov chain - Lapshin, A. L.; Лапшин, А. Л.; Лапшин, А. Л. (Institute of Mathematics, NAS of Ukraine, 1998)
We solve the problem of the estimation of a random state for a system with discrete time that is described by a system of linear difference equations with coefficients depending on a finite-valued Markov chain.